PROFIL RUMAHTANGGA MIGRAN PEREMPUAN DAN ANAK DI KABUPATEN BULELENG (Kasus Di Kecamatan Tejakula) - SRI ASTITI, Ni WAYAN (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 6, No. 1 Februari 2006, 2012)
Declining employment opportunity in rural areas in addition to declreasing young generation wants to work in agricultural sector has led to migration from rural to urban areas. This paper aims at finding out the household profile that has migrating members. The result shows that the number of migrating members is 131 (32% of the total household members). The age of migrants is relatively young with the average age 22.33 years for woman and 25.74 years for man. The type of dominant job held is as an employee of the private companies and services with the average of income per month at Rp 383,849.43 (for woman migrant) and Rp 400,898.47 (for man migrant). The way migrants moves to destination is self-planned for the reason of limited financial sources. The length of migrated ranges from one to three years with main destination to Kuta (Badung Regency) and Denpasar City. The socio-economic conditions of migrants are; most household (97.53%) has their own permanent house. Also, a large number of household (58.08%) has bathing and toilet facilities. The average of land size holding is 60 are, where 35 are is land owned and the rest is tenant land. The average of migrant household income is Rp 10,656,269.30 per year, where only 11.63% comes from agricultural sector and 88.37% from non-agricultural sector.
Keywords: Profile, Migrant, Household, Income